Exercise induced hypoglycaemic hyperinsulinism. Issue 3 (1st March 2001) - Meissner, T; Otonkoski, T; Feneberg, R; Beinbrech, B; Apostolidou, S; Sipilä, I; Schaefer, F; Mayatepek, E
Abstract : BACKGROUND: Hyperinsulinism in childhood is often caused by genetic defects involving the regulation of insulin secretion leading to recurrent episodes of hypoglycaemia. We report two patients with exercise induced hypoglycaemia. METHODS: Standardised short exercise tests with frequent blood glucose and plasma insulin measurements were performed in the patients and young healthy controls. RESULTS: Short term exercise resulted in insulin induced hypoglycaemia 15 to 50 minutes after the end of exercise. A massive burst of insulin secretion was observed within a few minutes of the start of exercise in both patients. By contrast glucose and insulin concentrations remained unchanged in healthy controls. CONCLUSIONS: Hyperinsulinaemic hypoglycaemia after moderate physical exercise represents a rarely described phenotype of hyperinsulinism with an as yet unknown defect in the regulation of insulin secretion. It should be suspected in individuals with recurrent exercise related syncope or disturbance of consciousness.